International working group identifies need for newborn screening for mucopolysaccharidosis type I but states that existing hurdles must be overcome - Parini, Rossella (Acta Paediatr, 2018)
AIM: Mucopolysaccharidosis type I is a lysosomal storage disorder that can result in significant disease burden, disability and premature death, if left untreated. The aim of this review was to elaborate on the diagnosis of mucopolysaccharidosis type I and the pros and cons of newborn screening. METHODS: An international working group was established to discuss ways to improve the early diagnosis of mucopolysaccharidosis type I. It consisted of 13 experts in paediatrics, rare diseases and inherited metabolic diseases from Europe and the Middle East. RESULTS: It is becoming increasingly clearer that the delay between symptom onset and clinical diagnosis is considerable for mucopolysaccharidosis type I and other rare lysosomal storage disorders, despite numerous awareness campaigns since therapies became available. Diagnosis currently depends on recognising the signs and symptoms of the disease. The practice of newborn screening, which is being explored by pilot programmes around the world, enables early diagnosis and consequently early treatment. However, these studies have highlighted numerous new problems and pitfalls that must be faced before newborn screening becomes generally available. CONCLUSION: Newborn screening for mucopolysaccharidosis type I offers the potential for early diagnosis and early pre‐symptomatic treatment, but existing hurdles need to be overcome.